PENGARUH PERILAKU KEPEMIMPINAN PADAKINERJAPEGAWAI DINAS TATAKOTAPEKANBARU - Widya Astuti (Universitas Riau, 2008)
It can not be denied that a person who plays an important role in an organization is aleader. The succees of leaders on taking the leadership of their employees is depend on theirleadership. One of the leadership approach is to study leadership behavioral while taking a leadershipon their employees to handle a job. This research is aimed to know a pattern of leadershipbehavior which emphasize on job centered and employee centered and to know is influence onofficers performance at Dinas Tata Kota Pekanbaru. Population of this research is taken from DinasTata Kota Pekanbaru are 60 people and all population to making sample. Research instrument is ina form of questioner with three option answer agree (score 3), less agree (score 2), disagree (score1 ). The result of this research indicates that leadership behavior at Dinas Tata Kota Pekanbarutends to apply employee centrered than job centered. The pattern ofleadership seems to improvethe performance at high category.